Association between SOFA score and risk of acute kidney injury in patients with diabetic ketoacidosis: an analysis of the MIMIC-IV database - Hua, Yiming; Ding, Ning; Jing, Huaizhi; Xie, Yifei; Wu, Hao; Wu, Yue; Lan, Beidi (Frontiers in Endocrinology, 2024)
IntroductionThe Sequential Organ Failure Assessment (SOFA) score is a widely utilized clinical tool for evaluating the severity of organ failure in critically ill patients and assessing their condition and prognosis in the intensive care unit (ICU). Research has demonstrated that higher SOFA scores are associated with poorer outcomes in these patients. However, the predictive value of the SOFA score for acute kidney injury (AKI), a common complication of diabetic ketoacidosis (DKA), remains uncertain. Therefore, this study aims to investigate the relationship between SOFA scores and the incidence of AKI in patients with DKA.MethodsThe study population was divided into two groups based on the median SOFA score (Q1: SOFA ≤3; Q2: SOFA >3). The primary endpoint was the incidence of AKI in patients with DKA. Secondary endpoints included renal replacement therapy (RRT) utilization and in-hospital mortality. Kaplan–Meier survival analysis, Cox proportional hazards models, and logistic regression models were employed to assess the association between SOFA and therisk of AKI in patients with DKA.ResultsOverall, 626 patients with DKA were included in this study, of which 335 (53%) were male. Kaplan–Meier survival analysis included that patients with higher SOFA scores experienced significantly increased cumulative incidences of AKI, higher rates of RRT utilization, and elevated in-hospital mortality. Furthermore, after adjusting for confounding factors, logistic regression and Cox proportional hazards analyses confirmed that SOFA scores remained significantly associated with the incidence of AKI in patients with DKA.ConclusionsOur study indicates that a high SOFA score is an independent risk predictor for the occurrence of AKI, the utilization of RRT, and in-hospital mortality in patients with DKA. The sofa score can be utilized as a biomarker to assess the risk of AKI in this patient population.